If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(8 + 2x)(5 + 2x) = (14.5 + 2x)(15 + 2x) Multiply (8 + 2x) * (5 + 2x) 3(8(5 + 2x) + 2x * (5 + 2x)) = (14.5 + 2x)(15 + 2x) 3((5 * 8 + 2x * 8) + 2x * (5 + 2x)) = (14.5 + 2x)(15 + 2x) 3((40 + 16x) + 2x * (5 + 2x)) = (14.5 + 2x)(15 + 2x) 3(40 + 16x + (5 * 2x + 2x * 2x)) = (14.5 + 2x)(15 + 2x) 3(40 + 16x + (10x + 4x2)) = (14.5 + 2x)(15 + 2x) Combine like terms: 16x + 10x = 26x 3(40 + 26x + 4x2) = (14.5 + 2x)(15 + 2x) (40 * 3 + 26x * 3 + 4x2 * 3) = (14.5 + 2x)(15 + 2x) (120 + 78x + 12x2) = (14.5 + 2x)(15 + 2x) Multiply (14.5 + 2x) * (15 + 2x) 120 + 78x + 12x2 = (14.5(15 + 2x) + 2x * (15 + 2x)) 120 + 78x + 12x2 = ((15 * 14.5 + 2x * 14.5) + 2x * (15 + 2x)) 120 + 78x + 12x2 = ((217.5 + 29x) + 2x * (15 + 2x)) 120 + 78x + 12x2 = (217.5 + 29x + (15 * 2x + 2x * 2x)) 120 + 78x + 12x2 = (217.5 + 29x + (30x + 4x2)) Combine like terms: 29x + 30x = 59x 120 + 78x + 12x2 = (217.5 + 59x + 4x2) Solving 120 + 78x + 12x2 = 217.5 + 59x + 4x2 Solving for variable 'x'. Reorder the terms: 120 + -217.5 + 78x + -59x + 12x2 + -4x2 = 217.5 + 59x + 4x2 + -217.5 + -59x + -4x2 Combine like terms: 120 + -217.5 = -97.5 -97.5 + 78x + -59x + 12x2 + -4x2 = 217.5 + 59x + 4x2 + -217.5 + -59x + -4x2 Combine like terms: 78x + -59x = 19x -97.5 + 19x + 12x2 + -4x2 = 217.5 + 59x + 4x2 + -217.5 + -59x + -4x2 Combine like terms: 12x2 + -4x2 = 8x2 -97.5 + 19x + 8x2 = 217.5 + 59x + 4x2 + -217.5 + -59x + -4x2 Reorder the terms: -97.5 + 19x + 8x2 = 217.5 + -217.5 + 59x + -59x + 4x2 + -4x2 Combine like terms: 217.5 + -217.5 = 0.0 -97.5 + 19x + 8x2 = 0.0 + 59x + -59x + 4x2 + -4x2 -97.5 + 19x + 8x2 = 59x + -59x + 4x2 + -4x2 Combine like terms: 59x + -59x = 0 -97.5 + 19x + 8x2 = 0 + 4x2 + -4x2 -97.5 + 19x + 8x2 = 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 -97.5 + 19x + 8x2 = 0 Begin completing the square. Divide all terms by 8 the coefficient of the squared term: Divide each side by '8'. -12.1875 + 2.375x + x2 = 0 Move the constant term to the right: Add '12.1875' to each side of the equation. -12.1875 + 2.375x + 12.1875 + x2 = 0 + 12.1875 Reorder the terms: -12.1875 + 12.1875 + 2.375x + x2 = 0 + 12.1875 Combine like terms: -12.1875 + 12.1875 = 0.0000 0.0000 + 2.375x + x2 = 0 + 12.1875 2.375x + x2 = 0 + 12.1875 Combine like terms: 0 + 12.1875 = 12.1875 2.375x + x2 = 12.1875 The x term is 2.375x. Take half its coefficient (1.1875). Square it (1.41015625) and add it to both sides. Add '1.41015625' to each side of the equation. 2.375x + 1.41015625 + x2 = 12.1875 + 1.41015625 Reorder the terms: 1.41015625 + 2.375x + x2 = 12.1875 + 1.41015625 Combine like terms: 12.1875 + 1.41015625 = 13.59765625 1.41015625 + 2.375x + x2 = 13.59765625 Factor a perfect square on the left side: (x + 1.1875)(x + 1.1875) = 13.59765625 Calculate the square root of the right side: 3.6875 Break this problem into two subproblems by setting (x + 1.1875) equal to 3.6875 and -3.6875.Subproblem 1
x + 1.1875 = 3.6875 Simplifying x + 1.1875 = 3.6875 Reorder the terms: 1.1875 + x = 3.6875 Solving 1.1875 + x = 3.6875 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.1875' to each side of the equation. 1.1875 + -1.1875 + x = 3.6875 + -1.1875 Combine like terms: 1.1875 + -1.1875 = 0.0000 0.0000 + x = 3.6875 + -1.1875 x = 3.6875 + -1.1875 Combine like terms: 3.6875 + -1.1875 = 2.5 x = 2.5 Simplifying x = 2.5Subproblem 2
x + 1.1875 = -3.6875 Simplifying x + 1.1875 = -3.6875 Reorder the terms: 1.1875 + x = -3.6875 Solving 1.1875 + x = -3.6875 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.1875' to each side of the equation. 1.1875 + -1.1875 + x = -3.6875 + -1.1875 Combine like terms: 1.1875 + -1.1875 = 0.0000 0.0000 + x = -3.6875 + -1.1875 x = -3.6875 + -1.1875 Combine like terms: -3.6875 + -1.1875 = -4.875 x = -4.875 Simplifying x = -4.875Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.5, -4.875}
| x^2-7x+12.25=.25 | | 3(n+2)=6-3(n+4) | | 4(20-2n)=4 | | 6x^2=3x+30 | | x-4/3+4/3=-x/2 | | 61/4-32/3 | | 2/7x=2 | | 497-x/3 | | 2(x-3)/5=12 | | e--36=-5 | | x=5+1 | | 5(n+2)+10=20 | | (6x^3-3x^2+4x)-(4x^2+3x+8)= | | 2x/3+20=30 | | 3(x-2)-x=12+5x | | -2/9r=-8 | | 4p-5=20 | | 2/3x-7/12x=5 | | 2y-6=4(y-2) | | -[10z-(21z+7)]=7+(10z+5) | | 3x-14+5x=10-4x | | 10xy-(2y-x)= | | 2m-18m=48 | | A-14a^4=2 | | 3(n+1)=12 | | 1.22y=y+4+1 | | -x^2+x-5=0 | | 9+y=14-2(y+1) | | y=5-3(2) | | 6.75x^2-21.8x+16=0 | | 5x+4=15x-104 | | -6(m+1)-m-6=-7(m+4)+16 |